Unpacking the toolbox of two-dimensional nanostructures derived from nanosphere templates. Issue 7 (25th April 2019) - Ke, Yujie; Ye, Shunsheng; Hu, Peng; Jiang, Hui; Wang, Shancheng; Yang, Bai; Zhang, Junhu; Long, Yi
Abstract : This review summarizes the advances in 2D nanostructures derived from nanosphere templates, from fabrication and properties to applications. Abstract : Controlled fabrication of micro-/nanostructures has been a long-standing research focus. The surface patterning technique via templates consisting of monolayer nanospheres is well recognized as an efficient, reliable, and inexpensive method to fabricate two-dimensional (2D) structural arrays. Recent rapid development in the synthesis of 2D patterned nanostructures via this method has led to diverse configurations, intriguing structure-induced properties, as well as novel functionalities for a broad range of applications. This review systematically summarizes the recent progress in 2D nanostructures from fabrications to applications. Particular emphasis is put on the rational design of structure-related functionalities for different applications. The diverse configurations derived from monolayer colloidal crystal templates are firstly introduced. Then, we classify the applications by discussing how the properties are benefited from the well-controlled nanostructures. We conclude the review by elaborating the promising functionalities in specific applications including sensors, solar cells, light-emitting diodes, field-effect transistors, photocatalysis, surface-enhanced Raman scattering, biological manipulation techniques, smart windows, photodetectors, transparent electronic devices, triboelectric nanogenerators, and so on, followed by perspectives on potential challenges and the future development.